2022
DOI: 10.1111/josh.13194
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Mexican High Schools

Abstract: BACKGROUND:We evaluated the association between availability of specific physical activity (PA) spaces and PA practices among adolescents within Mexican high schools (HS). METHODS: Data were collected through an online survey applied to principals or person in charge of 4023 Mexican HS during the 2015-2016 school year. Adequate PA was defined as moderate to vigorous intensity PA for ≥60 minutes/day, ≥5 days/week, whereas PA-specific spaces were considered those that were available and specifically designed/use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, the students spent most of their time sitting during recess, with little sport or physical activity. The trend is similar for adolescents in other developing countries [13,52,53]. Although the school allocated another 15 minutes every two days specifically for physical activity besides mandatory physical education (PE), most participating students were just standing instead of moving their bodies.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, the students spent most of their time sitting during recess, with little sport or physical activity. The trend is similar for adolescents in other developing countries [13,52,53]. Although the school allocated another 15 minutes every two days specifically for physical activity besides mandatory physical education (PE), most participating students were just standing instead of moving their bodies.…”
Section: Discussionmentioning
confidence: 62%
“…Although the school allocated another 15 minutes every two days specifically for physical activity besides mandatory physical education (PE), most participating students were just standing instead of moving their bodies. To achieve adequate physical activity, it was suggested that PE educators lead PE classes or allocate outdoor time [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have explored physical activity and eating behaviours among Mexican students, these have been centred primarily on children 8 or have used quantitative approaches 9 . For example, in a quantitative analysis of data from 4023 adolescents attending high schools in Mexico, only 31.7% of students reported meeting physical activity recommendations 10 . In this work, adequate facilities and a specialist physical education teacher were reported by students as facilitators of physical activity guideline attainment 10 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a quantitative analysis of data from 4023 adolescents attending high schools in Mexico, only 31.7% of students reported meeting physical activity recommendations 10 . In this work, adequate facilities and a specialist physical education teacher were reported by students as facilitators of physical activity guideline attainment 10 .…”
Section: Introductionmentioning
confidence: 99%